Hermetica Berolinensia I (Papyrus Berolinensis Graeca 9794) - Sowińska, Agata (Vox Patrum, 2024)
Papyrus Berolinensis Graeca 9794 was written in the 3rd century AD, most likely by a Christian compiler who included a fragment of a pagan text among Christian prayers – a Hermetic hymn from the first work of the "Corpus Hermeticum" collection. The subject of this paper is a translation into Polish, a philological study of the Hermetic fragment, technically called Hermetica Berolinensia I, taking into account the description of the Berlin Papyrus and its contents.